ACEHNESE WARS AND LEARNING FROM 12YEARS OF PEACE IN ACEH - Rafiie, Said Achmad Kabiru; Husni, Amir; Atah, Said (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
This paper aims to discuss the history of Acehnese wars and the progress of peace in Aceh after the signing of the Memorandum of Understanding between the Aceh Freedom Movement, or Gerakan Aceh Merdeka (GAM), and the Republic of Indonesia in Helsinki on August 15th, 2005. Prior to this, Aceh was a tense region and home to the longest armed conflict in Southeast Asia – underway since 1982. The people of Aceh were fighting to realize the concept of self-independence. However, the movement came to a stop when the devastating tsunami hit Aceh on December 26th, 2004. The purpose of this paper is to discuss the root of Acehnese wars. The paper will provide the current political, social, economic and cultural achievements since Aceh entered into a new chapter of peace. Using qualitative approach, the theory of inequality and conflict and Fanon’s ideas, this paper offers a comprehensive perspective on learning from Aceh wars and conflicts. This study found that the motive of wars in Aceh can be divided from group motive, private motivation, failure of social contract and environment scarcity. Moreover, the research confirms that social and economic progress in Aceh has not been as successful as its political achievements. Furthermore, in terms of culture, progress has been ambiguous. This paper aims to provide a better understanding of how to maintain peace in Aceh by addressing social, political, economic and cultural issues with the goal of attaining prosperity and well-being for the people of Aceh.